The Role of the East Java Provincial Bawaslu in Reporting on the 2024 General Election - septian, rizky; M. Agus. Muljanto (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Elections are a crucial pillar in Indonesia's democratic system, and their success heavily depends on transparent and participatory implementation. In the 2024 Election, the Election Supervisory Body (Bawaslu) of East Java Province played a key role in disseminating information through social media to enhance public understanding and participation. This study aims to analyze Bawaslu's role in election-related reporting in 2024, using Siagian's management theory, which includes planning, organizing, actuating, controlling, and evaluating. Employing a descriptive qualitative method, the research identifies challenges faced by Bawaslu, such as limited human resources, unequal infrastructure, and the spread of hoaxes. The findings indicate that while Bawaslu's communication strategies have successfully raised awareness and public participation, there are barriers in information outreach and digital literacy. This study offers recommendations for optimizing communication efforts through staff training, collaboration with mainstream media, and leveraging advanced technology. The findings are expected to contribute to strengthening Bawaslu's role in ensuring a more transparent and participatory election process in the future. Keywords: Bawaslu, News dissemination, Social media, Transparency, 2024 Election.